A ocupação do Neolítico Médio da Lapa do Fumo (Sesimbra) e sua cronologia absoluta - Cardoso, João Luís (2021)
Lapa do Fumo is a karst cavity located west of Sesimbra, dominating the ocean from the edge of the culminating platform of the Jurassic limestone massif that extends to Cape Espiche!. One of the main archaeological results of the excavations carried out in the 1960’s by Eduardo da Cunha Serrão and Gustavo Marques was the identification of the so-called "Red Layer", due to the impregnation of red ocher, used ritually in the framework of the funeral ceremonies then performed there. The chronology of this layer was dubious, due to the existence of two statistically different dates, one, older, using fragments of charcoal, which pointed to the beginning of the Middle Neolithic, another, more recent, using human bones, which indicated the Final Neolithic. Everything indicated that it would be a deposit of the Final Neolithic, bearing in mind the occurrence of some unknown archaeological artifacts in the Middle Neolithic, such as schist decorated plaques, some head pins and carinated bowls. Considering the importance of clarifying the chronology of this ritual deposit, which is frequently mentioned in publications of the specialty, a fragment of calcaneus collected in 1965 in a layer immediately based on the "Red Layer" was dated by AMS technique. The chronology obtained is still inserted in the Middle Neolithic, confirming the result of the first date that placed the formation of the "Red Layer" in the Middle Neolithic. Consequently, the result previously obtained on human bones must refer to the upper layer, whose accumulation extended at least over the Final Neolithic period, thus explaining the presence of artifacts characteristic of that time, which were previously attributed to the "Red Layer" by the two authors of the excavations. The chronology of the "Red Layer" was thus definitively clarified, which corresponds to an important contribution to the funerary rituals observed in natural caves in Extremadura during the Middle Neolithic.